Natronoglomus mannanivorans gen. nov., sp. nov., beta-1,4-mannan utilizing natronoarchaea from hypersaline soda lakes - Sorokin, Dimitry Y.; Elcheninov, Alexander G.; Bale, Nicole J.; Sinninghe Damsté, Jaap S.; Kublanov, Ilya V. (Frontiers in Microbiology, 2024)
Beta-mannans are insoluble plant polysaccharides with beta-1,4-linked mannose as the backbone.We used 3 forms of this polysaccharide, (pure mannan, glucomannan and galactomannan) to enrich for haloarchaea capable of utilizing mannans for growth. Four mannan-utilizing strains obtained in pure cultures were closely related to each other on the level of the same species. Furthermore, another strain selected from the same habitats with a soluble beta-1,4-glucan (xyloglucan) was also able to grow with mannan. Phylogenomic analysis placed the isolates into a separate lineage of the new genus level within the family Natrialbaceae of the class Halobacteria. The strains are moderate alkaliphiles and extremely halophilic aerobic saccharolytics. Apart from the 3 beta-mannan forms, they can also grow with cellulose, xylan, and xyloglucan. Functional genome analysis of two representative strains demonstrated a presence of several genes coding for extracellular endo-beta-1,4-mannanase from the GH5_7 and 5_8 subfamilies and GH26 family of glycosyl hydrolases. Furthermore, a large spectrum of genes encoding other glycoside hydrolases potentially involved in hydrolysis of cellulose and xylan were also identified in the genomes. Comparative genomics analysis also showed a presence of similar endo-beta-1,4-mannanase homologues in the cellulotrophic genera Natronobiforma and Halococcoides. On the basis of unique physiological properties and the results of phylogenomic analysis, the novel mannan-utilizing halolarchaea are proposed to be classified into a new genus and species Natronoglomus mannanivorans gen. nov., sp.nov. with the type strain AArc-m2/3/4 (=JCM 34861=UQM 41565).